A Recursive Methodology to Determine the Mechanical Response of Thin Laminated Plates in Bending - Lisboa,Tales de Vargas (2017)
ABSTRACT: The paper's objective is to present the development of a recursive methodology which is based on Adomian Decompostion Method in order to evaluate the mechanical response of thin laminated plates in linear bending. By the equivalent layer concept, the linear relation between the equivalent stresses and the strains, namely ABD matrix, is established. When viewed by the Adomian Decompostion Method perspective, it generates an interesting idea: each layer influence on the plate's response can be recursively inserted into a base solution by a rearrangement of the plate's properties. This base solution is previously obtained and it is, in this paper, an isotropic plate response for the same loading and boundary conditions. This approach can significantly increase optimization and delamination studies, given the simplicity on the layers modification, both in fiber orientation and constitutive properties, as these are considered on the recursive procedure. The pb-2 Rayleigh-Ritz Method is used to approximate the solution space and to generate analytic response surfaces. The methodology is applied to symmetrical and unsymmetrical stacking cases for different boundary conditions sets and loading types and the obtained responses are compared to those found on the literature. A study of case complements the methodology analysis: a simplified landing gear door is modeled considering a set of loading conditions as well as different stacking configurations. Good correspondence was found in all studied cases.